Insegnanti si diventa L'esperienza di Tirocinio nei Corsi di laurea magistrale in Scienze della Formazione primaria - Bolognesi, Ivana (La Scuola Se - Open Access, 2018)
The volume outlines the internship experiences developed by numerous Teacher Education Degree Courses arising after the D.M. 249/2010, which established the Master's Degree Course in Primary Education. The individual essays develop the contributions presented in the International Conference "Insegnanti si diventa", organized by the Department of Educational Sciences "G. M. Bertin" (Bologna, 1-2 October 2015).